2012
DOI: 10.1111/j.1752-0606.2012.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Validity of the Affirmative Training Inventory: Assessing the Relationship between Lesbian, Gay, and Bisexual Affirmative Training and Students’ Clinical Competence

Abstract: This study established the validity and factor structure of the Affirmative Training Inventory (ATI; T. S. Carlson, C. R. McGeorge & M. Rock, unpublished) as a measure of lesbian, gay, and bisexual (LGB) affirmative clinical training. Additionally, this study examined the latent associations among the subscales of the ATI and the Sexual Orientation Counselor Competency Scale (Bidell, 2005) utilizing a sample of 248 master’s and doctoral couple and family therapy students. The findings from this study provide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 38 publications
(84 reference statements)
4
70
0
Order By: Relevance
“…A review of the literature indicates that: (a) supervision is often considered one of the most important mediums through which therapy is taught to trainees; (b) LGB issues are not adequately being addressed within supervision; and, (c) there is a dearth of empirical studies that assess the extent to which marriage and family therapy (MFT) faculty and supervisors are attending to LGB issues within clinical training and supervision (Carlson et al, 2012;Rock et al, 2010), and specifically to the ways in which these issues relate to the experiences of LGB supervisees (e.g., Charlés, Thomas, & Thornton, 2005; Hernandez & Rankin, 2008;Long & Serovich, 2003).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…A review of the literature indicates that: (a) supervision is often considered one of the most important mediums through which therapy is taught to trainees; (b) LGB issues are not adequately being addressed within supervision; and, (c) there is a dearth of empirical studies that assess the extent to which marriage and family therapy (MFT) faculty and supervisors are attending to LGB issues within clinical training and supervision (Carlson et al, 2012;Rock et al, 2010), and specifically to the ways in which these issues relate to the experiences of LGB supervisees (e.g., Charlés, Thomas, & Thornton, 2005; Hernandez & Rankin, 2008;Long & Serovich, 2003).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Unfortunately, there are few empirical studies that specifically address the experience of LGB supervisees (Burkard et al, 2009). The few that do exist, however, highlight the importance of creatingLGB-affirming environments for LGB supervisees (e.g., Burkard et al, 2009;Lark & Croteau, 1998) and for supervisees working with LGB clients (e.g., Aducci & Baptist, 2011;Bahr, Brish, & Croteau, 2000;Carlson, McGeorge, & Toomey, 2012;Long, 2002;Rock, Carlson, & McGeorge, 2010).Researchers have noted the importance of providing safety and LGB-affirmative environments for LGB trainees and supervisees (e.g., Burkard et al, 2009;Lark & Croteau, 1998). For example, Lark and Croteau's (1998) study of 14 self-identified LGB doctoral students' mentoring relationship with faculty found that when students felt affirmed and safe in their LGB identities within the training environment, they were able to fully engage in their training.…”
mentioning
confidence: 99%
See 3 more Smart Citations